2017
DOI: 10.1017/s0007114517000617
|View full text |Cite
|
Sign up to set email alerts
|

Association between phytosterol intake and colorectal cancer risk: a case–control study

Abstract: A study in rodent models showed that phytosterols protected against colon carcinogenesis, probably by inhibiting dysregulated cell cycle progression and inducing cellular apoptosis. However, epidemiological studies on the relationship between phytosterols and colorectal cancer risk are quite limited. The aim of this study was to investigate dietary phytosterol intake in relation to colorectal cancer risk in the Chinese population. A case-control study was conducted from July 2010 to June 2016, recruiting 1802 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 39 publications
2
43
0
1
Order By: Relevance
“…Second, uneven distribution of the highest and lowest intakes of phytosterols may have resulted in heterogeneity in the summary analysis and reduced the reliability of the conclusions. Third, almost all of the studies included in our meta-analysis used food frequency questionnaires (FFQ) or a validated FFQ to collect dietary information except one conducted by Walcott et al [56], which used the National Cancer Institute's Health Habits and History Questionnaire (HHHQ). Fourth, validated data were not available for dietary questionnaires in several studies; however, we conducted a stratified analysis and found no significant change in the association between dietary phytosterol consumption and cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…Second, uneven distribution of the highest and lowest intakes of phytosterols may have resulted in heterogeneity in the summary analysis and reduced the reliability of the conclusions. Third, almost all of the studies included in our meta-analysis used food frequency questionnaires (FFQ) or a validated FFQ to collect dietary information except one conducted by Walcott et al [56], which used the National Cancer Institute's Health Habits and History Questionnaire (HHHQ). Fourth, validated data were not available for dietary questionnaires in several studies; however, we conducted a stratified analysis and found no significant change in the association between dietary phytosterol consumption and cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…These compounds are structurally similar to cholesterol and characterized by anti-carcinogenic and anti-antherogenic properties [44]. The potential mechanisms of the protective effect of navy bean-derived phytosterols against CRC include inhibition of the cell cycle progression, induction of cellular apoptosis and the reduction of cellular oxidative stress [45]. β-sitosterol is a component of beans that has been shown to inhibit growth of COLO 320 DM cells (IC50 266.2 μM), by scavenging reactive oxygen species and inducing apoptosis; as well as suppressing the expression of β-catenin and PCNA antigens in human colon cancer cells [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…β-sitosterol, a phytosterol found in OO, inhibited significantly the growth of COLO 320 DM cells, in a dose-dependent way, caused apoptosis by scavenging ROS, and suppressed the expression of beta-catenin and proliferating cell nuclear antigen (PCNA) in human colon cancer cells [42]. A case-control study carried out in a Chinese population, showed that the consumption of phytosterols, including β-sitosterol, campesterol and campestanol was associated with a reduction of CRC risk making it a potential anticancer drug for colon carcinogenesis [92].…”
Section: Anti-inflammatory Immunomodulatory and Other Anticancer mentioning
confidence: 99%